Sustainable landscape, soil and crop management practices enhance biodiversity and yield in conventional cereal systems. Issue 3 (26th January 2021) - Redlich, Sarah; Martin, Emily A.; Steffan‐Dewenter, Ingolf
Abstract: Input‐driven, modern agriculture is commonly associated with large‐scale threats to biodiversity, the disruption of ecosystem services and long‐term risks to food security and human health. A switch to more sustainable yet highly productive farming practices seems unavoidable. However, an integrative evaluation of targeted management schemes at field and landscape scales is currently lacking. Furthermore, the often‐disproportionate influence of soil conditions and agrochemicals on yields may mask the benefits of biodiversity‐driven ecosystem services. Here, we used a real‐world ecosystem approach to identify sustainable management practices for enhanced functional biodiversity and yield on 28 temperate wheat fields. Using path analysis, we assessed direct and indirect links between soil, crop and landscape management with natural enemies and pests, as well as follow‐on effects on yield quantity and quality. A paired‐field design with a crossed insecticide‐fertilizer experiment allowed us to control for the relative influence of soil characteristics and agrochemical inputs. We demonstrate that biodiversity‐enhancing management options such as reduced tillage, crop rotation diversity and small field size can enhance natural enemies without relying on agrochemical inputs. Similarly, we show that in this system controlling pests and weeds by agrochemical means is less relevant than expected for final crop productivity. Synthesis and applications . Our study highlights soil, crop and landscape management practices that can enhance beneficial biodiversity while reducing agrochemical usage and negative environmental impacts of conventional agriculture. The diversification of cropping systems and conservation tillage are practical measures most farmers can implement without productivity losses. Combining local measures with improved landscape management may also strengthen the sustainability and resilience of cropping systems in light of future global change. Abstract : Our study highlights soil, crop and landscape management practices that can enhance beneficial biodiversity while reducing agrochemical usage and negative environmental impacts of conventional agriculture. The diversification of cropping systems and conservation tillage are practical measures most farmers can implement without productivity losses. Combining local measures with improved landscape management may also strengthen the sustainability and resilience of cropping systems in light of future global change. Abstrakt: Die moderne Landwirtschaft, geprägt durch hohe Inputs, wird oft als Bedrohung für die Artenvielfalt und Ökosystemdienstleistungen, und als Risiko für die Nahrungsmittelsicherheit und unsere Gesundheit angesehen. Ein Wandel in Richtung nachhaltiger und dennoch ertragreicher Landwirtschaft ist unausweichlich. Doch es mangelt an ganzheitlichen Studien, in denen gezielte Bewirtschaftungsmethoden auf Feld‐ und Landschaftsebene evaluiert werden. Gleichzeitig kann oft nicht unterschieden werden, ob Ertragszuwächse von biodiversitäts‐geförderten Ökosystemleistungen oder dem oft überproportionalen Einfluss von Bodencharakteristiken und Agrochemikalien stammen. In dieser Studie nutzen wir einen realen Ökosystemansatz, um nachhaltige Bewirtschaftungsmethoden zu identifizieren, welche die funktionelle Artenvielfalt und den Ertrag auf 28 temperaten Weizenfeldern beeinflussen. Mit Hilfe von Pfadanalysen evaluieren wir die direkten und indirekten Zusammenhänge zwischen Boden‐, Pflanzen‐ und Landschaftsmanagement mit Räubern und Schädlingen, sowie Folgeeffekte für Ertragsquantität und ‐qualität. Durch ein gepaartes Flächendesign in Verbindung mit einem gekreuzten Insektizid‐Dünger Experiment korrigieren wir für den relativen Einfluss von Bodencharakteristiken und Agrochemikalien. Wir zeigen, dass biodiversitätsfördernde Maßnahmen wie reduzierte Bodenbearbeitung, diverse Fruchtfolgen und kleine Feldgrößen natürliche Räuber unabhängig von dem Einsatz von Agrochemikalien fördern. Gleichzeitig scheint der Einsatz von Pflanzenschutzmitteln zur Bekämpfung von Schädlingen und Unkräutern nur einen geringfügig positiven Einfluss auf Weizenerträge in diesem System zu haben. Synthesis and applications . Unsere Studie identifiziert Maßnahmen des landwirtschaftlichen Boden‐, Pflanzen‐ und Landschaftsmanagements, die Nützlinge fördern und gleichzeitig den Bedarf an Agrochemikalien (und damit negative Auswirkungen der Landwirtschaft auf die Umwelt) reduzieren. Der Einsatz vielfältiger Anbausysteme und eine schonende Bodenbearbeitung sind zwei mögliche Praktiken, die viele Landwirte gut umsetzen können, ohne schwerwiegende Ertragsverluste zu erleiden. In Verbindung mit einem verbesserten Landschaftsmanagement könnten diese lokalen Maßnahmen außerdem die Nachhaltigkeit und Resilienz landwirtschaftlicher Systeme im Hinblick auf den zukünftigen Klimawandel stärken.